EVALUASI TINGKAT KEPUASAN PENGGUNA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT MENGGUNAKAN MODEL END USER COMPUTING SATISFACTION DI RSUD PANEMBAHAN SENOPATI BANTUL - Amelia Handayani Burhan; Windadari Murni Hartini (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2018)
Hospital Management Information System (SIMRS) role in in both medical or non-medical data storage of patient which processed into information, in the form of reporting to assist management in determining the decisions and policies related to hospital services. The purpose of this study was to evaluate the level of user satisfaction Hospital Management Information System using a Model End User Computing Satisfaction in hospitals Panembahan Senopati Bantul.The research design used in this study was cross sectional research design. Samples were selected by simple random sampling with a sample size of 91. Analysis of data using computer programs with Univariate analysis by means of descriptive and bivariate analysis using product moment correlation statistic test. As for the degree of trust that is used is 95% and Î± = 0:05. Results from this study is the level of performance SIMRS approval by the element content of 74.03%, format element 68.50% , the element of accuracy 68.24% , timeliness element of 69.67%, and the element of ease of use at 71,39%. SIMRS user satisfaction level of 71.90%. Correlation test results obtained using the Pearson correlation correlation value of 0.719 and a significance value of 0.000. Results of determination (R2) in regression models known summary of 0.510 or 51.0%. The conclusion of this study is the degree of agreement on the performance SIMRS and the level of user satisfaction in hospitals Panembahan SIMRS Senopati Bantul not reached 80% of the expected, and there is significant correlation between performance SIMRS with SIMRS user satisfaction.